ANALISI SUMBER DAN PENGGUNAAN MODAL PADA KSP CU KHATULISTIWA BAKTI ABSTRACT - Budiman, Budiman; Asriati, Nuraini; Budiman, Jumardi (Universitas Tanjungpura, 2024)
This study aims to find out where the sources of working capital come from and what are the working capital used for at KSP CU Khatulistiwa Bakti Pontianak City. The method used in this study is a qualitative descriptive approach, namely qualitative research is descriptive and tends to use analysis and emphasis on the depth of data obtained by researchers. The source of data in this study is the financial statements of the KSP CU Khatulistiwa Bakti balance sheet, Pontianak City. Data collection techniques are interviews, observation, and documentation. The data collection tools are data reduction, data presentation and verification. In this study, the authors calculate the source and use of capital using financial statement data in the form of a balance sheet. From the analysis of sources and use of capital, it can be seen that the increase in working capital in CUs is due to the source of capital being greater than the use of working capital.